2020
DOI: 10.1016/j.neo.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

BRAF inhibition in melanoma is associated with the dysregulation of histone methylation and histone methyltransferases

Abstract: The development of mutant BRAF inhibitors has improved the outcome for melanoma patients with BRAF V600E mutations. Although the initial response to these inhibitors can be dramatic, sometimes resulting in complete tumor regression, the majority of melanomas become resistant. To study resistance to BRAF inhibition, we developed a novel mouse model of melanoma using a tetracycline/doxycycline-regulated system that permits control of mutant BRAF expression. Treatment with doxycycline leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
1
14
1
Order By: Relevance
“…This provides further evidence that, in melanoma, EZH2 mediates miR-129-5p expression downstream of constitutive active BRAF signaling. Although previous studies showed a reduction of H3K27me3 during treatment with BRAFi or MEKi in melanoma [62,63] we could not confirm these changes in our experiments. These different results may be explained by using low doses of treatment (0.4 µM Vemurafenib or 10 nM Trametinib) or shorter treatment times (48 h).…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…This provides further evidence that, in melanoma, EZH2 mediates miR-129-5p expression downstream of constitutive active BRAF signaling. Although previous studies showed a reduction of H3K27me3 during treatment with BRAFi or MEKi in melanoma [62,63] we could not confirm these changes in our experiments. These different results may be explained by using low doses of treatment (0.4 µM Vemurafenib or 10 nM Trametinib) or shorter treatment times (48 h).…”
Section: Discussioncontrasting
confidence: 95%
“…We have now demonstrated that, in melanoma, EZH2 represses miR-129-5p, dependent on constitutive active BRAF signaling. After treatment of BRAF mutated melanoma cells with BRAFi or MEKi, we observed a reduction of EZH2 protein as well as mRNA, as shown previously for melanoma [ 62 , 63 ]. Additionally, specific inhibition of EZH2 induces miR-129-5p expression in BRAF mutated melanoma cell lines, independent from their BRAFi response status, while BRAF wildtype cells and normal melanocytes show no changes of expression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The methylation of histone H3K4, R8, R17, K26, K36, K79, H4R3, and K12 can activate gene transcription ( 42 , 43 ). However, the methylation of histone H3K9, K27, K56, H4K5, and K20 inhibits gene transcription, confirming the complexity of epigenetic regulation of histone methylation ( 44 ). Interestingly, under different conditions, the methylation of histone H3R2 can activate and inhibit transcription ( 33 ).…”
Section: Histone Methylation Modificationmentioning
confidence: 80%
“…These two types of epigenetic changes appear to influence each other in the deposition during mammalian development and carcinogenesis; histone methylation appears to direct DNA methylation patterns, while DNA methylation may serve as a model for establishing certain histone changes [ 32 ]. Moreover, in CM, DNA methylation is gaining increased importance in PD-related immune therapy [ 48 ], while histone alterations are associated with BRAF-targeted therapy [ 49 ].…”
Section: Epigenetics: Another Layer Of Information In Gene Expression Regulationmentioning
confidence: 99%